Paths to Internationalisation of Small and Medium-sized Enterprises in Ukraine - Glinkowska-Krauze, Beata; Chebotarov, Iegor; Chebotarov, Viacheslav (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: The defining objectives of the study are the following three. First, to classify the level of real development of internationalisation in Ukrainian SMEs. To accomplish this goal, the authors summarise the theory and methodology defining the field of internationalization. They also present their own empirical studies on Ukrainian small and medium-sized enterprises (SMEs). Second, they analyse the main forms, motivational factors and barriers to the internationalisation of Ukrainian SMEs. Finally, they discuss the development of strategies and mechanisms for activating the internationalisation of SMEs in Ukraine. Research Design & Methods: The study used qualitative research, including a survey of the literature and our own empirical research (detailed interviews with Ukrainian entrepreneurs, survey questionnaire, and experimental assessments of scientists from Ukraine and Poland on this subject). Findings: The present condition of the internationalisation of Ukrainian small and medium-sized enterprises is assessed, and its obstacles and motives have been identified. In the context of the European Union’s experience in regulating small and medium-sized businesses, the most promising strategies and sectors of the economy have been classified. It is in these sectors that Ukrainian small and medium-sized enterprises should gain the greatest competitive advantages. Lastly, mechanisms for promoting the internationalisation of Ukrainian SMEs are defined. Implications / Recommendations: In modern conditions the internationalisation of Ukrainian small and medium-sized enterprises is at an early stage. It does currently extend substantively beyond export-import operations. In Ukraine, enterprises that internationalise tend to do so upon or near their inception. The main approach to stimulating the internationalisation of Ukraine’s SME sector is to develop effective state regulatory policy adapted to the contemporary norms and standards of the European Union. The results of the study have shown that Ukrainian SMEs can gain their greatest competitive advantages in the global market in industries including agriculture (primarily, “eco” and “green”), alternative and renewable energy production and IT technologies. Contribution: Research fills a research gap in the field of internationalisation of Polish and Ukrainian small and medium-sized enterprises.